The effect of Accounting Information System characteristics on the Internal Audit Effectiveness among companies traded in Iraqi stock exchange: testing the moderating role of experience - Almaliki, Oday Jasim Mohammed (2020)
The aim of this research was to investigate the effect of Accounting Information System (AIS) characteristics on the Internal Audit Effectiveness (IAE) in companies traded in Iraqi stocks exchange by focusing on the moderating effect of experience. The selected characteristics were reliability, flexibility, timeliness, integration, and relevance. The research theoretical foundation was built based on the agency and contingency theories. A quantitative approach using Structural Equation Modeling (SEM) was utilized as the main research design. The data was collected from a group of respondents comprising accountants (n=175), auditors (n=85), account managers (n=60), and audit managers (45) who were selected through a simple random sampling technique. The data was analyzed to determine the effects. A survey questionnaire was developed and verified for its construct validity based on judgments of eight experts. A pilot test was conducted to investigate the questionnaire reliability involving 40 respondents selected from several companies. Exploratory factorial analysis was conducted on 100 respondents in several companies to verify that the research variables that could be used in the actual study. The actual survey questionnaire was distributed to 365 respondents and the data were analyzed using confirmatory factorial analysis in order to determine the relationship between AIS and IAE variables. The research results indicated that all selected AIS characteristics have different significant effects on IAE. The significant effects were relevance ( =0.273, p<0.05), followed by flexibility ( =0.150, p<0.05), integration ( =0.109, p< 0.05), reliability ( =0.098, p<0.05) and timeliness ( =0.095, p<0.05). Moreover, experience moderated the relationships among flexibility ( =0.111, p<0.05) and integration ( =0.094, p<0.05). In conclusion, relevance is the most dominant AIS factor that affects IAE, and experience serves as an influential moderator between AIS and IAE. In implication, companies should focus on experience to enhance the effectiveness of AIS and IAE systems and to increase their accountants and auditors knowledge and skills.